Estudos in vitro e in vivo da própolis vermelha brasileira: potencial antibacteriano, antiparasitário e antiviral frente a microrganismos patogênicos - Silva, Nagela Bernadelli Sousa (2024)
Infectious diseases continue to be an important cause of thousands of deaths annually around the world. Therefore, the objective of this study was to evaluate the antimicrobial, antiviral and antiparasitic activity of Brazilian Red Propolis (BRP) against microorganisms that cause endodontic infections, Chikungunya virus and Toxoplasma gondii, using in vitro, in vivo and in silico approaches, in addition to carrying out evaluations toxicology of these products. Antimicrobial activity was determined by the broth dilution method and synergistic activity by the checkerboard assay. Antibiofilm activity was evaluated by staining with 2% crystal violet and counting microorganisms. In vivo infection was performed on Caenorhabditis elegans AU37 larvae and in silico analysis was performed using molecular docking. The effect on modulating the growth of T. gondii was evaluated using a β-galactosidase colorimetric assay. In the first study, BRP demonstrated antiperiodontopathogenic activity against all microorganisms evaluated, as well as antibiofilm activity against monospecies and multispecies biofilms. Furthermore, it was able to inhibit Chikungunya virus infection by up to 97%. In C. elegans, propolis did not demonstrate toxicity at the therapeutic concentrations determined in the study. In the second study, BRP demonstrated antibacterial and antifungal activity against all microorganisms included. The crude extract demonstrated additive activity in combination with amphotericin B against C. albicans (ATCC 28366). Furthermore, the BRP samples significantly inhibited biomass production and reduced the number of viable cells in the biofilm, in addition to reducing cell aggregation and causing damage to the cell wall of the microorganisms present in the biofilm. The highest concentrations of the crude extract and Gutiferone E of BRP increased the survival of infected and treated larvae and reduced the risk of death. The isolated substances Gutiferone E and Oblongifolin B inhibited the intracellular proliferation of T. gondii and demonstrated several targets of action against bacteria and T. gondii in silico analysis. The results presented in the two articles are promising and constitute a basic study so that in the future BRP can be used as a medicine against clinically relevant microorganisms.